The Nadzir’s Role in Waqf Empowerment for General Welfare (Case Study in the Nadzir of Universitas Islam Malang Foundation) - Anisa Fitria Utami; Agus Suman; Asfi Manzilati (e-2477-1929)
The purpose of this research is to find out the role of the nadzir in developing waqf assets for general welfare. The management of productive waqf for general welfare that conducted by The Nadzir of Univesitas Islam Malang Foundation. The Nadzir of Universitas Islam Malang Foundation received 2 bilion Rupiahs funds from Kementerian Agama that acted as the waqif. The waqf fund are from Anggaran Belanja dan Pendapatan Negara Perubahan with purpose as the pilot program of productive waqf fund management. In order to run the role, The Nadzir of Universitas Islam Malang Foundation is stick with the sharia law and UU No. 41 Tahun 2004. The role of Universitas Islam Malang’s nadzir is suitable with the duties and roles that listed on UU No 41 Tahun 2004. The duties and roles are first, accepting and administrating the waqf asset. Second, managing and developing waqf asset through build VIP Rooms, Al-Khaibar Minimarket and Go Fish Restaurant. Third, keep the waqf asset through pledging the waqf asset to Bank Muamalat and fourth, reporting the waqf asset management to Kementerian Agama as waqif.